2018
DOI: 10.1155/2018/5728957
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potential Drug-Drug Interactions with Medications Prescribed to Geriatric Patients in a Tertiary Care Hospital

Abstract: Background and Objectives The drugs most commonly implicated in major potential interactions are those used in the day-to-day clinical management of elderly patients with chronic diseases. This study is planned to evaluate the profile of drug-drug interactions in the medications prescribed to elderly population and also to identify the possible predictors for potential drug-drug interactions in the elderly. Methods This cross-sectional study included patients aged above 60 years with a minimum of two drugs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
43
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 22 publications
9
43
2
2
Order By: Relevance
“…In our study, one of the most common reasons PLHIV switched ART in the past was to reduce the number of medicines or pills they had to take, and 2 in 3 PLHIV were willing to switch to an ART with fewer medications as long as their viral load was suppressed. Concurrent use of multiple medications may considerably increase risk of drug-drug interactions, especially among people with concomitant medications (22)(23)(24), and this concern was well reflected in our study. Recent studies have established that the number of drug-drug interactions increases with the number of medications (22)(23)(24).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In our study, one of the most common reasons PLHIV switched ART in the past was to reduce the number of medicines or pills they had to take, and 2 in 3 PLHIV were willing to switch to an ART with fewer medications as long as their viral load was suppressed. Concurrent use of multiple medications may considerably increase risk of drug-drug interactions, especially among people with concomitant medications (22)(23)(24), and this concern was well reflected in our study. Recent studies have established that the number of drug-drug interactions increases with the number of medications (22)(23)(24).…”
Section: Discussionsupporting
confidence: 55%
“…Concurrent use of multiple medications may considerably increase risk of drug-drug interactions, especially among people with concomitant medications (22)(23)(24), and this concern was well reflected in our study. Recent studies have established that the number of drug-drug interactions increases with the number of medications (22)(23)(24). Most non-HIV conditions reported by PLHIV in our study were chronic conditions largely found in the general population, such as mental health conditions, hypertension, and hypercholesterolemia, which may require long-term management with medications.…”
Section: Discussionsupporting
confidence: 55%
“…Another study conducted by Shetty V et al reported the 663 pDDIs in total 209 patients . 12.75% prescriptions [17] in current study showed at least One pDDI, whereas this value was 83.3 % in the study done by Shetty V et al and 78.2% in the study [17] conducted by Tesfaye ZT et al . [18] Among the prescriptions with at least One pDDI, majority had 1 to 2 pDDIs per prescription in our study, the nding which was in line with that reported by Shetty V et al .…”
Section: C) Potential Drug-drug Interactions (Pddis)contrasting
confidence: 60%
“…The study report showed that the elderly patients on average took 2 to 5 drugs, and poly-pharmacy occurred in 20–50% of elderly patients [ 2 , 3 ]. Consequently, adverse drug reactions and drug interactions are more common and more serious in the elderly [ 14 , 15 ]. Frequent checks of used medications, particularly for drug interactions and use of medications, are considered appropriate for the elderly [ 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%